The responsible organization - Lennick, Doug (FTPress Delivers, 2011)
"This Element is an excerpt from Moral Intelligence: Enhancing Business Performance and Leadership Success (ISBN: 9780132349864) by Doug Lennick and Fred Kiel. What it takes to build the "responsible organization": lessons from leaders and a handy "responsibility checklist""--Resource description page.
Resource description page (viewed Sept. 13, 2010)
Keywords: Business ethics; Leadership -- Moral and ethical aspects; Success in business -- Moral and ethical aspects; Businesspeople -- Ethics; Morale des affaires; Leadership; Aspect moral; Succès dans les affaires; Aspect moral; Gens d'affaires; Morale; BUSINESS & ECONOMICS / Business Ethics; Leadership; Moral and ethical aspects; Electronic resource